2013
DOI: 10.1371/journal.pone.0075356
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Inhibits Tumor Growth and Induces Apoptosis in a Breast Cancer Xenograft Mouse Model: The Role of p38 MAPK and ROS

Abstract: Due to narrow therapeutic window of cancer therapeutic agents and the development of resistance against these agents, there is a need to discover novel agents to treat breast cancer. The antitumor activities of thymoquinone (TQ), a compound isolated from Nigella sativa oil, were investigated in breast carcinoma in vitro and in vivo. Cell responses after TQ treatment were assessed by using different assays including MTT assay, annexin V-propidium iodide staining, Mitosox staining and Western blot. The antitumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(123 citation statements)
references
References 39 publications
7
113
2
1
Order By: Relevance
“…Another study also show production of free radicals and P38 phosphorylation. in breast cancer cell line, thus inducing proapoptotic potential 61 .This is just opposite what we observe in normal cells, where it scavenges fRs. Thus it role in normal and cancer cells are different.…”
contrasting
confidence: 72%
“…Another study also show production of free radicals and P38 phosphorylation. in breast cancer cell line, thus inducing proapoptotic potential 61 .This is just opposite what we observe in normal cells, where it scavenges fRs. Thus it role in normal and cancer cells are different.…”
contrasting
confidence: 72%
“…Since then, increasing numbers of studies have focused on TQ in cancer therapy. Numerous in vitro and in vivo studies have investigated the antitumor activity of TQ in several types of cancer (6,14,19,(27)(28)(29)33). In tumor protein p53-null myeloblastic leukemia HL-60 cells, TQ induced apoptosis through an intrinsic signaling pathway (34).…”
Section: Discussionmentioning
confidence: 99%
“…In human multiple myeloma cells, TQ inhibits proliferation, induces apoptosis and exerts a chemosensitization effect through suppressing signal transducer and activator of transcription 3 (acute-phase response factor) activation (35), and decreases F-actin polymerization and Bcl-2/Bcl-2 like 1 expression (36). TQ-induced apoptosis has been indicated to be mediated by reactive oxygen species generation (29,33,37) and the mitogen-activated protein kinase 14 signaling pathway (33). In 2004, Gali-Muhtasib et al (38) reported that TQ triggered apoptotic cell death in human colorectal cancer cells via a p53-dependent mechanism, and in 2008, Gali-Muhtasib et al (31) demonstrated that TQ triggered inactivation of the stress response pathway sensor checkpoint kinase 1 and contributed to apoptosis in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were repeated 3 times for each concentration. Then, the cytotoxicity effects of TQ on PC3 cells were assessed by MTT assay (24,25). Briefly, after treating cells for 48 hours, the culture medium was removed and cells were exposed to 100 µL colorless RPMI and 10 µL MTT (5 mg/mL in phosphate buffered saline (PBS) added to each well and incubated for 4 hours.…”
Section: Cell Culture and Mtt Assaymentioning
confidence: 99%